The influence of school accountability incentives on Advanced Placement access: Evidence from Pennsylvania - Beach, Paul; Zvoch, Keith; Thier, Michael (Education Policy Analysis Archives, 2019)
This study employed hierarchical piecewise growth modeling and two interrupted time series models to examine the effect of introducing an Advanced Placement (AP) school accountability incentive on AP access in Pennsylvania. Specifically, we examined whether adoption of an advanced course access accountability indicator was associated with an increase in AP course offerings initially and in the three years after the policy intervention. We also analyzed if the indicator differentially affected schools we hypothesized as sensitive or nonsensitive to the policy and examined demographic differences between those school groups. Pennsylvania’s AP accountability incentive was associated with an initial increase in schools’ AP course offerings, but the trajectory of change during the post-policy intervention period did not differ from the pre-policy baseline period. Also, the sizeable gap between schools with the most and fewest AP course offerings did not narrow across time. Instead, the gap widened. Our results suggest that adoption of AP school accountability incentives may not be a long-term solution to improving AP access for all schools or narrowing disparities in access between schools. We call for examinations in other states to determine if, and under what conditions, AP accountability incentives increase AP course offerings while narrowing access disparities.